Evaluation of Bio-Markers in Vaccinated And Unvaccinated COVID-19 Patients With Comorbidities - Islam, Md Hafizul; Khaled, Saifuddin Md; Islam, Md Rafat Mushfiqul (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: SARS-CoV-2 typically causes pneumonia and ARDS has created massive disruptions and loss of human lives around the world and continues to pose several diagnostic and therapeutic challenges. Measurement of different biomarker levels help to assess the severity and progression of the disease, as many studies shown. Besides vaccination helps to reduce both infection rate and severity as recent studies report. So, study on biomarkers on COVID-19 would create great public health impact to control the pandemic. This study investigates the impact of vaccination on biomarker profiles and its role in providing protection against severe outcomes in high-risk populations. Materials and methods: A cross-sectional study was conducted comprising fifty (50) vaccinated and fifty (50) unvaccinated COVID patients. Different biomarkers levels were measured and compared in various groups of COVID patients based on their vaccination status. Results: In total, 100 patients were included in the study (One-dose vaccinated patients: 25, two-dose vaccinated patients: 25, unvaccinated: 50), of whom 46 were male and 54 were female. There was no statistical difference in mean between vaccinated and unvaccinated patients in terms of age and gender. The most common comorbidities were hypertension (n=49) diabetes mellitus (n=28) and obesity (n=30). Ferritin levels were significantly lower in two-dose vaccinated patients compared to one-dose and unvaccinated groups (p=0.018). D-dimer and procalcitonin levels were significantly lower in two-dose vaccinated patients compared to one-dose and unvaccinated groups (p = 0.002, 0.004) respectively (p=0.004). No significant differences were observed in hemogram or CRP levels among unvaccinated, one-dose, and two-dose vaccinated patients. Conclusions: Unvaccinated COVID-19 patients with comorbidities had higher serum ferritin, D-dimer, and procalcitonin levels than vaccinated patients. JCMCTA 2025 ; 36 (1) : 114-118